Reactions to the Market : Small Farmers in the Economic Reshaping of Nicaragua, Cuba, Russia, and China - Enríquez, Laura J. (Rural studies series (University Park, Pa.), 2010)
"Analyzes the reaction of existing and former socialist countries to neoliberalism. Examines economic transitions in agriculture and the reconfiguration of socialism in Russia, China, Nicaragua, and Cuba"--Provided by publisher.